2022
DOI: 10.3389/fpubh.2022.1026532
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in income among psychiatrists in China: Findings from a national survey

Abstract: BackgroundGender income disparity in healthcare settings is a longstanding issue around the globe, but such evidence among Chinese psychiatrists is scarce. This study investigated whether gender income differences exist among physicians in China.MethodsData came from the 2019 national survey data of 4,520 psychiatrists in major public psychiatric hospitals across China. Self-reported monthly income after tax (in Chinese Yuan, CNY) by participants at all professional ranks was assessed. Average monthly income b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Almost one-third (32%) of women reported being discriminated against, compared to only 5% of men (Wright et al 2003). In China, female senior psychiatrist earned significantly less money than their corresponding males (Han et al 2022). The study conducted by Singer et al 2022, showed that although the majority of pediatrcians were women in the top 27 grant-funded department in the United States, men had more likelihood to hold an endowed chair than women.…”
Section: Discussionmentioning
confidence: 99%
“…Almost one-third (32%) of women reported being discriminated against, compared to only 5% of men (Wright et al 2003). In China, female senior psychiatrist earned significantly less money than their corresponding males (Han et al 2022). The study conducted by Singer et al 2022, showed that although the majority of pediatrcians were women in the top 27 grant-funded department in the United States, men had more likelihood to hold an endowed chair than women.…”
Section: Discussionmentioning
confidence: 99%